2012
DOI: 10.1007/s00213-011-2632-6
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine challenge decreases yohimbine binding to α2 adrenoceptors in Landrace pig brain

Abstract: These data suggest that the binding of [11C]yohimbine to α2 adrenoceptors may be displaceable by increases in synaptic concentrations of the endogenous ligand, NA, and possibly dopamine, suggesting the possibility that [11C]yohimbine may be used as a surrogate marker of NA release in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…When the BP ND declined significantly in response to the amphetamine challenge, the Inhibition plot yielded the V ND value that must be known to calculate the BP ND of radiotracers with displaceable accumulation in all parts of the brain. Similar findings were reported in recent PET studies in pigs, where [ 11 C]-yohimbine binding was significantly displaced by competition with endogenous transmitters, as shown by a decline of the V T in response to acute amphetamine treatment, 6 although the binding potential was not calculated because the magnitude of V ND varied among the few subjects studied.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When the BP ND declined significantly in response to the amphetamine challenge, the Inhibition plot yielded the V ND value that must be known to calculate the BP ND of radiotracers with displaceable accumulation in all parts of the brain. Similar findings were reported in recent PET studies in pigs, where [ 11 C]-yohimbine binding was significantly displaced by competition with endogenous transmitters, as shown by a decline of the V T in response to acute amphetamine treatment, 6 although the binding potential was not calculated because the magnitude of V ND varied among the few subjects studied.…”
Section: Discussionsupporting
confidence: 88%
“…However, partial volume effects cannot fully explain the [ 11 C]yohimbine binding in striatum, because recent in vivo studies in pigs with much larger brains show [ 11 C]-yohimbine binding in caudate nucleus and putamen that is similar to the binding in cortical regions. 5, 6 …”
Section: Discussionmentioning
confidence: 99%
“…For verifying if the metabolic and hemodynamic effects of octopamine in the liver are mediated by adrenergic receptors, we performed experiments using several antagonists: (a) yohimbine (α 1 and α 2 -antagonist), (b) prazosin (mainly α 1 -antagonist) [28–30] and (c) propranolol (non-specific β-antagonist) [31,32]. Livers from fed rats were used in all experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Despite some antihypertensive properties, it generally increases blood pressure at rest, which is thought to be mediated via central antagonism of a2 adrenergic receptors (Biaggioni et al, 1994). Our earlier studies have found that in tracer concentrations, yohimbine exhibits high selectivity for a2 sites in vivo in pigs (Jakobsen et al, 2006) which is displaceable by amphetamine challenge (Landau et al, 2012a). Central a2 NA receptors are widely expressed pre-synaptically primarily on NA cell bodies and dendrites in the locus coeruleus (LC).…”
Section: Introductionmentioning
confidence: 99%